2015
DOI: 10.3141/2484-06
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Ramp Metering Based on On-Ramp Saturation Time Synchronization

Abstract: In this paper, a coordinated ramp-metering approach is proposed; the approach is based on the synchronization of the time it takes for an on-ramp to run out of space. The time that congestion and the associated capacity drop can be prevented at a freeway bottleneck by means of ramp metering depends on the available ramp space for temporarily storing the vehicles. For a single on-ramp, the available space and thus the metering time at the bottleneck are often limited. By means of coordination, upstream storage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…It can take into account the whole system compared with local ramp metering. Present studies have indicated CRM solutions are more efficient than isolated ones [16]- [18].…”
Section: Introductionmentioning
confidence: 89%
“…It can take into account the whole system compared with local ramp metering. Present studies have indicated CRM solutions are more efficient than isolated ones [16]- [18].…”
Section: Introductionmentioning
confidence: 89%
“…Traffic-responsive RM is based on the real-time traffic conditions in a freeway network. Several field and laboratory experiments have shown the effectiveness of traffic-responsive RM (Hourdakis and Michalopoulos, 2002; Khoo, 2011; Kotsialos and Papageorgiou, 2004; Landman, 2015). Although traffic-responsive RM offers potentially strong results to manage the motorway traffic at merging regions, the strictly limited space of ramps makes it difficult to reach satisfactory results (Papamichail et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In some cases (Carlson et al, 2014; Hegyi et al, 2005a), in order to mitigate the interference of the on-ramp and mainline traffic flows, the benefits of the on-ramp outflow are greatly sacrificed, where the on-ramp queue length is simply considered a constraint condition. Other methods of integrating the RM and VSL are not suitable in certain conditions (Carlson et al, 2012; Gomes and Horowitz, 2006; Khoo, 2011; Kotsialos and Papageorgiou, 2004; Kotsialos et al, 2002; Landman, 2015; Ma et al, 2015). For example, when the merging region is congested, on-ramp vehicles are not allowed to flow into the merging region and the right of way of on-ramp vehicles is deprived.…”
Section: Introductionmentioning
confidence: 99%
“…Their effectiveness might, however, be suboptimal because full utilization of the coordinated ramp storage spaces is not explicitly targeted. Hence, by doing so, some of the more recently proposed algorithms-such as HERO (9) and the algorithm proposed in Landman et al (10) based on ramp saturation time synchronization-do have the potential to maximize the metering duration on a freeway bottleneck. However, none of the above mentioned methods address which ramps to coordinate to further decrease the total system delay, given the prevailing network characteristics.…”
Section: Introductionmentioning
confidence: 99%